(untitled) (Ciencias de la Ingeniería y Aplicadas, 2025)
This study evaluates the impact of smart home devices on energy efficiency and power quality in a residential dwelling in Pelileo, Ecuador. The research was conducted through a two-stage monitoring process using a smart meter and a Fluke 1735 power analyzer, both before and after the implementation of smart devices. Results indicate a 10.9% reduction in total energy consumption, highlighting economic potential. However, an increase in harmonic distortion led to a 3.4% reduction in power factor, raising concerns about energy quality degradation. The study underscores the importance of addressing power quality issues when implementing energy-saving technologies in residential settings.